2015
DOI: 10.1016/j.smrv.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Social interactions, emotion and sleep: A systematic review and research agenda

Abstract: Sleep and emotion are closely linked, however the effects of sleep on socio-emotional task performance have only recently been investigated. Sleep loss and insomnia have been found to affect emotional reactivity and social functioning, although results, taken together, are somewhat contradictory. Here we review this advancing literature, aiming to 1) systematically review the relevant literature on sleep and socio-emotional functioning, with reference to the extant literature on emotion and social interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(134 citation statements)
references
References 129 publications
4
120
0
1
Order By: Relevance
“…This would seem to be at odds with the anxiolytic effects for which oxazepam is used. One explanation could be that oxazepam caused increased sleepiness, which is known to cause worse ratings of subjective experience [78]. While oxazepam is not mainly prescribed for its hypnotic properties, our reaction time results showed that participants in the oxazepam group did show a decrease in psychomotor vigilance, consistent with this interpretation.…”
Section: Discussionsupporting
confidence: 85%
“…This would seem to be at odds with the anxiolytic effects for which oxazepam is used. One explanation could be that oxazepam caused increased sleepiness, which is known to cause worse ratings of subjective experience [78]. While oxazepam is not mainly prescribed for its hypnotic properties, our reaction time results showed that participants in the oxazepam group did show a decrease in psychomotor vigilance, consistent with this interpretation.…”
Section: Discussionsupporting
confidence: 85%
“…The PSQI has good internal consistency and discriminant validity (Buysse et al, 1989). This past-month sleep measure served as a covariate to separate the role of acute sleep patterns from longer-term problems, which may affect inflammation and behavior through different mechanisms (Beattie et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Gender was included to account for husband-wife differences in behavior and inflammatory responses to conflict. Own and partner chronic sleep problems (PSQI) served to separate the role of acute sleep patterns from longer-term sleep problems, which may affect inflammation and behavior through different mechanisms (Beattie et al, 2015). Own or partner marital satisfaction was added to parse out the effects of general relationship quality on inflammation from sleep-specific effects (Robles et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep serves many homeostatic processes and is essential for physical health, cognitive performance, and socio-emotional functioning (e.g., Beattie et al, 2015; Scullin and Bliwise, 2015; Patrick et al, 2017). One important aspect of sleep is the extent to which one perceives it to be free from disturbances, i.e., sleep quality.…”
Section: Introductionmentioning
confidence: 99%